Lattice calculation of D- and B-meson semileptonic decays, using the clover action at β = 6.0 on APE - Chris Allton (Physics Letters B, 1995)
We present the results of a high statistics lattice calculation of hadronic form factors relevant for $D-$ and $B-$meson semi-leptonic decays into light pseudoscalar and vector mesons. The results have been obtained by averaging over 170 gauge field configurations, generated in the quenched approximation, at $β=6.0$, on a $18~3 × 64$ lattice, using the $O(a)$-improved SW-Clover action.From the study of the matrix element $<K~-\vert J_μ \vert D~0>$, we obtain $f_+ (0)=0.78± 0.08$ and from the matrix element $<\bar K~{* 0}\vert J_μ \vert D~+>$ we obtain $V(0)=1.08± 0.22$, $A_1(0)=0.67± 0.11$ and $A_2(0)=0.49± 0.34$. We also obtain the ratios $V(0)/A_1(0)=1.6± 0.3$ and $A_2(0)/A_1(0)= 0.7± 0.4$. Our predictions for the different form factors are in good agreement with the experimental data, although, in the case of $A_2(0)$, the errors are still too large to draw any firm conclusion. With the help of the Heavy Quark Effective Theory (HQET) we have also extrapolated the lattice results to $B$-meson decays. The form factors follow a behaviour compatible with the HQET predictions. Our results are in agreement with a previous lattice calculation, performed at $β=6.4$, using the standard Wilson action.